Display of cellulases on the cell surface of Saccharomyces cerevisiae for high yield ethanol production from high-solid lignocellulosic biomass - Matano, Yuki; Hasunuma, Tomohisa; Kondo, Akihiko (Bioresource technology, 2012)
► Economically feasible ethanol production process requires high-titer ethanol. ► High-solid cellulosic materials were fermented using a cellulase-displaying yeast. ► Pretreated biomass was converted to ethanol with 89% theoretical yield within 72h. ► Cell-surface engineering successfully reduced commercial enzyme addition. ► The yeast hydrolyzed cellulose that was not hydrolyzed by commercial cellulase. Economically feasible processes for industrial cellulosic ethanol production requires increasing the final ethanol titer during fermentation due to the high energy demands of the subsequent ethanol distillation. In the present study, high-yield ethanol production was achieved by short-term liquefaction and fermentation of lignocellulose biomass in a novel drum-type rotary fermentation system using a yeast strain developed for cell-surface display of fungal endoglucanase, cellobiohydrolase, and β-glucosidase. In the presence of 10FPU/g-biomass cellulase added, the recombinant cellulolytic strain produced 1.4-fold higher ethanol (89% of theoretical yield) from high-solid (200g-dry weight/L) rice straw within 72h of fermentation than wild type strain. Cell-surface engineering successfully reduced the amount of commercial enzyme required for the fermentation of cellulose. This study demonstrates that cellulases displayed on the yeast cell surface are capable of hydrolyzing cellulose that was not hydrolyzed by commercial cellulases, leading to increased sugar utilization for improved ethanol production.